Analisis Kesulitan Belajar Daring Mahasiswa Tadris Matematika Pada Materi Aljabar - Ayu Lestari; Wulida Arina Najwa; Annisagita Sungga Dirgantari (JUMAT: Jurnal Matematika, 2023)
This study aims to describe the various difficulties faced by students during brave learning in abstract algebra courses. The research subjects were 4 semesters VI students of Tadris Mathematics at IAIN Fattahul Muluk Papua who teach Abstract Algebra courses. Data collection techniques use observation and interviews of the think-aloud type which make it possible to vilify information through thinking subjects during the learning process. The results of the research show that the difficulties faced by each student vary. However, in general, the difficulties faced by students are understanding the material when using the WhatsApp, Google Classroom, and Zoom Cloud Meeting applications. Comprehension through the WhatsApp Group is less effective because the learning outcomes obtained by students are still low when compared to Google Classroom and Zoom Cloud Meetings.